Photoinduced electron transfer in a meso-linked Zn(II)porphyrin-Zn(II) phthalocyanine/C60-pyridyl supramolecular system - Urbani, Maxence; Osati, Samira; Kuhri, Susanne; Guldi, Dirk Michael; Torres, Tomas (Journal of Porphyrins and Phthalocyanines, 2013)
A non-covalent supramolecular complex combining porphyrin (Por), phthalocyanine (Pc) and fullerene [C], was obtained through zinc metal-pyridine coordination between a covalently meso-linked heterodimer ZnPor-ZnPc (4) and a N-pyridylfulleropyrrolidine derivative (5). The complexation was studied in toluene by absorption and fluorescence binding studies, and evidenced that the coordination of the N-pyridylfulleropyrrolidine (5) occurs preferentially through the zinc ion center of ZnPc (log K > 6.0) rather than ZnPor (log K = 5.23). Steady-state and time-resolved spectroscopies evidenced that upon selective excitation of either the Por, or the Pc moiety in [(ZnPor-ZnPc)∪C], the singlet excited state of Pc was generated efficiently in both cases (either from singlet-singlet energy transfer from Por* to Pc, or directly after selective excitation of the Pc moiety). Next, an electron transfer occurred from the Pc* to the C to generate the charge-separated specie [(ZnPor-ZnPc )∪C]. Finally, the back electron transfer afforded the Pc triplet excited state rather than the ground state. The introduction of a covalent meso-linkage between Por and Pc in the heterodimer 4 and in the supramolecular assembly 4∪5 induces appreciable differences toward the photo-induced processes and the binding constants in comparison with other β-covalently linked analogue systems. © 2013 World Scientific Publishing Company.